An Analysis of Determinant Factors in the Management of Madrasah Ibtidaiyah in the Archipelago Region - Nur Hasanah; Ridhwan Latuapo; Eko Wahyunanto Prihono; Oscar Ndayizeye (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to identify the dominant factors influencing the management of madrasah ibtidaiyah in the archipelago. The research employs a quantitative approach with an ex post facto design, utilizing accreditation data from Madrasah Ibtidaiyah. Twenty-nine madrasahs were selected as samples using purposive sampling, based on the criterion of being accredited between 2021 and 2023 in Maluku Province. Principal Component Analysis (PCA) was applied to analyze analyze the data. The findings reveal that four principal components were identified out of 13 initial components, cumulatively accounting for 83.3% of the total variance. This sample confirms the model’s reliability in explaining madrasah management in the archipelago. These four principal components are: (1) Strategic leadership and madrasah quality assurance (64.9%), (2) Madrasah resource management (7.4%), (3) A conducive madrasah environment (6.3%), and (4) Partnership synergy with madrasah resources (4.7%). Further analysis indicates that strategic leadership and quality assurance exert the most significant influence, which is crucial in ensuring effective Madrasah management and the sustainability of educational quality in the archipelago. The implications of this study suggest that to enhance madrasah management effectiveness, madrasah leaders should reinforce internal quality assurance systems, optimize resource management, establish a conducive learning environment, and foster stronger partnerships with the community and other stakeholders. These findings provide a basis for formulating education policies that are more inclusive and adaptable to the geographical conditions of the archipelago, enabling it to compete effectively.